2019
DOI: 10.1088/1741-4326/ab1610
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of discharges with ion cyclotron range of frequencies using local gas injection in EAST

Abstract: In view of improving Ion Cyclotron Range of Frequencies (ICRF) wave coupling in EAST (Experimental Advanced Superconducting Tokamak) necessary to obtain high-power discharges, two series of experiments in L-mode were devoted to the use of local gas injection as a tool to increase density in front of the antennas.During the first session, the quantity of deuterium simultaneously puffed from five different poloidal positions on each side of one ICRF antenna was gradually increased. Steady gas puffing on this ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…However, other synergistic mechanisms may also contribute to the beneficial effect of LHCD on the ICRF coupling observed experimentally. A similar observation was also made in EAST [25], but so far, more experiments are needed to fully identify the dominant underlying mechanism.…”
Section: Icrf Wave Couplingsupporting
confidence: 67%
See 2 more Smart Citations
“…However, other synergistic mechanisms may also contribute to the beneficial effect of LHCD on the ICRF coupling observed experimentally. A similar observation was also made in EAST [25], but so far, more experiments are needed to fully identify the dominant underlying mechanism.…”
Section: Icrf Wave Couplingsupporting
confidence: 67%
“…Further details about the ICRF system are given in the next section. All antennas (LHCD and ICRF) are actively cooled allowing for long pulse operation whilst gas can also be injected from different valves either at the top, or near antennas limiters to try to increase the density at the edge and improve the wave coupling [24,25]. Gas can be injected from over ten different valves but the one that will be used for the present study are essentially materialized by yellow circles in Fig.…”
Section: General Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The edge plasma density can be effectively increased by puffing the fueling gas locally in the main chamber of the machine. Recently, many experimental and numerical studies have been made of the maximization of ICRF power coupling with local gas puffing in many devices, such as AUG [43,44,[66][67][68], JET [45,69,70], DIII-D [71,72], EAST [73,74], WEST [75], ITER [46] and DEMO [76]. It is found that compared to divertor gas puffing, midplane gas puffing close to the antenna can increase the coupling resistance by ∼120% and top gas puffing by ∼20%-40%.…”
Section: Icrf Power Couplingmentioning
confidence: 99%
“…• Locally increase the density by fueling the plasma from valves magnetically connected to the antenna and ideally as close as possible to the middle plane [24,25] • Increase the frequency of the waves, which must remain compatible with an efficient scenario for heating the plasma (discussed in the next section) k // can be minimized at two different stages:…”
Section: Properties Of 120mhz Icrf Fast (Fw-dashed Lines) and Slow (S...mentioning
confidence: 99%